Peli1 Contributions in Microglial Activation, Neuroinflammatory Responses and Neurological Deficits Following Experimental Subarachnoid Hemorrhage - Huang, Xue-Ping; Peng, Jian-Hua; Pang, Jin-Wei; Tian, Xiao-Cui; Li, Xin-Shen; Wu, Yue; Li, Yong; Jiang, Yong; Sun, Xiao-Chuan (Frontiers in Molecular Neuroscience, 2017)
Early brain injury (EBI) following subarachnoid hemorrhage (SAH) is closely associated with neuroinflammation. Microglial activation is an early event that leads to neuroinflammation after SAH. Peli1 is an E3 ubiquitin ligase that mediates the induction of pro-inflammatory cytokines in microglia. Here we report Peli1 contributions in SAH mediated brain pathology. An SAH model was induced by endovascular perforation in adult male C57BL/6J mice. Peli1 was markedly induced in mice brains in a time-dependent manner and was predominantly expressed in CD16/32-positive microglia after SAH. Using genetic approaches, we demonstrated that decreased Peli1 significantly improved neurological deficits, attenuated brain edema, reduced over-expression of pro-inflammatory cytokine IL-6 and modified apoptotic/antiapoptotic biomarkers. In addition, Peli1 downregulation suppressed ERK and JNK phosphorylation levels via the downregulation of cIAP1/2 expression, subsequently reducing iNOS expression after SAH. Therefore, these findings demonstrate that Peli1 contributes to microglia-mediated neuroinflammation in EBI by mediating cIAP1/2 activation, thus promoting the activation of MyD88-dependent MAPK pathway after experimental SAH. Our findings also showed that Peli1 could promote the expression of M1 microglia polarization biomarker CD16/32 and iNOS after SAH. Targeting Peli1 exerts neuroprotective effects during EBI after SAH, thus could provide potential option for prevention-therapy in high-risk individuals.